The Battle of Taste Under The Tent A Study of the Togal Tradition on Makeang Community in North Maluku - M Ridha AJAM; Rudi TAWARI (Indonesia Strategic Sustainability, 2022)
This article studies the tradition of togal in Makeang communities in North Maluku. This tradition faced various dynamics, one of which is a matter of taste. The young and old generations have different taste when togal performed. The young generation does not appreciate togal, while the older generation is still very appreciative. The assumption is that if the young generation does not appreciate anymore, the existence of the togal is being threatened. The reason is, the generation that has the role in the sustainability of this tradition has not positive attitude. By using the qualitative research methods, this study reveals that tastes are a subjective area that cannot be debated. Tastes are the truth of everyone. However, in most cases, conflicts often occur. The generation that has an interest in togal is involved in the battle of tastes with the generation who are not interested in the context of performance. The older generation wants to play togal, while the younger generation rejects as a music of party (performance). This battle occurs because there is a different opinion between of them. Thus, there is a negotiation process in solving the problem. If the older generation is more dominant, the party will be held with the music of togal. If there is a way of agreement, then the time for the party that takes all night is agreed to be two parts. The first part is for togal, while the second for modern music.